2003
DOI: 10.1002/jcb.10740
|View full text |Cite
|
Sign up to set email alerts
|

GSTP1 CpG island hypermethylation as a molecular biomarker for prostate cancer

Abstract: Somatic hypermethylation of CpG island sequences at GSTP1, the gene encoding the pi-class glutathione S-transferase, appears to be characteristic of human prostatic carcinogenesis. To consider the potential utility of this epigenetic alteration as a biomarker for prostate cancer, we present here a comprehensive review of the literature describing somatic GSTP1 changes in DNA from prostate cells and tissues. GSTP1 CpG island hypermethylation has been detected in prostate cancer DNA using a variety of assay tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
118
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(122 citation statements)
references
References 74 publications
1
118
1
Order By: Relevance
“…A variety of techniques to detect DNA with GSTP1 CpG island hypermethylation in prostatic tissues and bodily fluids have been described (9). We used the previously described restriction endonuclease quantitative PCR method (12).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of techniques to detect DNA with GSTP1 CpG island hypermethylation in prostatic tissues and bodily fluids have been described (9). We used the previously described restriction endonuclease quantitative PCR method (12).…”
Section: Methodsmentioning
confidence: 99%
“…GSTP1 encodes an enzyme that acts as a carcinogen detoxifier by catalyzing conjugation reactions with reduced glutathione (7). Somatic GSTP1 CpG island hypermethylation has been noted in >90% of prostate cancer tissues, whereas it has not been observed in the normal prostate (9). It is important to note that DNA with GSTP1 CpG island hypermethylation is rarely seen elsewhere in the body, occurring with significance only in cancers of the liver and breast (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We were initially alerted to a potential problem involving GC bias when GSTP1, which is highly methylated at its CpG islandassociated promoter in prostate cancer and is unmethylated in normal cells (Song et al 2002;Nakayama et al 2004), showed little differential enrichment at the probe-level on the Affymetrix promoter tiling arrays after MeDIP enrichment and WGA of prostate cancer (LNCaP) and normal prostate epithelial cells (PrECs) (see Supplemental Fig. 3A; Coolen et al 2010).…”
Section: Medip and Mbdcap Enrich Different Fractions Of The Genome Bamentioning
confidence: 99%
“…Molecular markers could have important applications in staging and the clinical diagnosis breast cancer [33]. Their Usage for cancer staging and personalization of treatment in time of diagnosis can improve patient care [34].…”
Section: Stage Of Diseasementioning
confidence: 99%